Desenvolvimento de filme biodegradável contendo sobrenadante de Pediococcus acidilactici CE51 livre de células como embalagem protetora de carne de frango e bovina - Pinho, Gabriela da Silva (2025)
This study aimed to evaluate the bioconservative effect of a biodegradable film with cell-free supernatant (CFS) of P. acidilactici CE51 on chicken and beef meat contaminated with L. monocytogenes and E. faecium. Starch and carboxymethyl cellulose-based films were produced with 0%, 50% and 100% CFS. Physical properties and antimicrobial action were evaluated. The solubility and opacity of the films were higher in those containing 100% CFS. There was an increase in tensile strength and an increase in antimicrobial action as the CFS concentration increased. In chicken meat, films with ≥ 50% CFS reduced E. faecium after 4 days, reaching 0.8 Log CFU/ml with 100% CFS in 8 days at 4ºC. For L. monocytogenes, the greatest reduction (0.8 Log CFU/ml) occurred with 100% CFS after 8 days. In beef, films with 100% CFS reduced E. faecium (0.88 CFU/ml) after 8 days, while films with 50 and 100% CFS reduced L. monocytogenes from 4 days onwards, reaching 1.9 CFU/ml at 8 days. Films containing SLC from P. acidilactici CE51 showed promise as biopreservatives in food.